Misuse Of Women's Protective Laws Against Men In India. - Lakshmana Kumar, M.; Saleem Akram, P. (Journal of Neonatal Surgery, 2025)
The protective laws enacted to safeguard women's rights in India have been misused to harass & exploit men, leading to a crucial social & legal challenge. This research examines the misuse of women's protective laws, particularly the Protection of Women from Domestic Violence Act (PWDVA), 2005, & Section 498A of the Indian Penal Code (IPC). The research reveals that false cases are filed to extort money, gain custody of children, or exact revenge, causing immense emotional & financial distress to innocent men. The lack of penal provisions for false complaints & the non-bailable nature of these laws contribute to their misuse. This paper analyzes the judicial responses, societal factors, & legislative loopholes that facilitate this misuse. It argues that while women's empowerment is crucial, the rights of men should also be protected to prevent abuse of these laws. The research recommends stringent penalties for false complainants, mandatory investigations, & judicial reforms to prevent the misuse of women's protective laws.